Общежитие: [сборник] / Владимир Зазубрин - Зазубрин Владимир Яковлевич (Библиотека "Сибирских огней", 1990)
Экземпляры: ф.8 (1993) / Инвентарный номер: 36903 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: З-16 / ГРНТИ: 17.82.30 / ББК: 84(2Рос=Рус)6-4